Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time! - Stephen Thorpe (Biodiversity Data Journal, 2013)
In 1921, Scutellista caerulea was imported and released in Nelson, New Zealand, for the biological control of pest scale insects. It was thought to have failed to establish, and is therefore currently considered to be absent from the New Zealand fauna. On 17 April 2013, a live specimen was captured in the wild in Auckland.